(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
On the occasion of the 101st anniversary of the work The Thaumaturgical Kings (1924) and the 80th anniversary of Marc Bloch’s assassination by the Gestapo in 1944, we focus this note not only on the high significance of these dates, but also to commemorate the presence of Bloch’s historiographic personality among us from the personal experience of 1986, on the occasion of Bloch’s birth centenary, since both in Caracas and in Barquisimeto (Venezuela) academic events were held to revalue the intellectual heritage of this Frenchman of Jewish origin who, in a short time, 57 years of life, carried out an intellectual work that placed the scientificity of knowledge at a high level. This is a task of inestimable value, even today in the 21st century. His historiographic legacy is also a legacy of episteme and techniques of historical research of universal scope. Translated with DeepL.com (free version)